Continuing Professional Education Needs Assessments in Emergency Medical Services - Scott Frasard (Adult Education Research Conference, 2012)
Emergency Medical Service (EMS) educators are faced with the daunting task of providing prehospital care providers with quality continuing professional education (CPE) while meeting the needs of various stakeholders. This study sought to find how EMS educators make CPE offering decisions by examining three primary areas: the sources of information used to generate CPE topic ideas, factors that influence decision making, and strategies used to collect and analyze data. Additionally, a comprehensive list of CPE offered by study participants from the last two years was generated, which demonstrates how these three areas drive EMS CPE. Keywords: Emergency Medical Services, EMS, continuing education, continuing professional education, learning needs, needs assessment, EMS educator, EMS instructor
Keywords: Emergency Medical Services; EMS; continuing education; continuing professional education; learning needs; needs assessment; EMS educator; EMS instructor